Design and construction of a normal mode helical antenna; Design and construction of a pyramidal horn antenna; Design of dipole antenna for mobile communication system; Design of axial mode helical anttena for line of sight communication; Design of a monopole antenna for mobile stations / [mikrofilem] - Alagappa Nagappan; Fadzil Yahaya; Nadaraj Govindasamy; R Preman Narayanan; Suppiah Narayanasamy (Kuala Lumpur : UTM, 1994)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1994